Mitochondrial dysfunction characterises the multigenerational effects of maternal obesity on MASLD - Anneleen Heldens; Milton Antwi; Louis Onghena; Tim Meese; Yannick Gansemans; Joél Smet; Ellen Dupont; Xavier Verhelst; Sarah Raevens; Hans Van Vlierberghe; Arnaud Vanlander; Filip Van Nieuwerburgh; et al. (JHEP Reports)
Background & Aims: Although maternal obesity is an independent risk factor for metabolic dysfunction-associated steatotic liver disease (MASLD), the pathogenesis remains unclear. We aimed to evaluate the effect and mechanisms of multigenerational maternal Western diet (WD) on MASLD progression, and test drug candidates. Methods: Female mice were fed WD from 8 weeks before breeding initiation with a normal chow (NC)-fed male, throughout pregnancy and lactation. Male offspring were weaned onto NC or WD and assessed at the age of 24 days, 10 weeks, and 16 weeks (n = 5–11 per group). Additionally, offspring from dams with hepatic insulin receptor knockout were evaluated (n = 9–12 per group). Serum fibroblast growth factor 21 (FGF21) and mitochondrial open reading frame of 12S rRNA-c (MOTS-c) were measured in adolescents with MASLD with or without a history of maternal obesity. The therapeutic efficacy of FGF21, semaglutide and an amylin analogue was assessed from 8 to 16 weeks of age (n = 8–12 per group). Results: Starting from weaning age, maternal WD feeding aggravated body weight gain, insulin resistance, steatosis, and inflammation. Fibrosis was only observed in offspring exposed to maternal WD. Mechanistically, the latter exhibited reduced OXPHOS activity. Isolated maternal hepatic insulin resistance partially recapitulated offspring inflammation and fibrosis. Notably, OXPHOS was also downregulated in a transcriptomic dataset of maternal WD feeding in non-human primates. Serum FGF21 and MOTS-c correlated with MASLD severity and maternal obesity in adolescents. Particularly FGF21 treatment ameliorated steatohepatitis and mitochondrial function. Conclusions: Maternal WD aggravates MASLD in male offspring starting from weaning age, with mitochondrial dysfunction contributing to disease severity. This was reversed by FGF21 agonism. Impact and implications: The underlying mechanisms of maternal obesity contributing to metabolic dysfunction-associated steatotic liver disease (MASLD) severity in the offspring are not completely understood. Our study characterises the impact of multigenerational maternal Western diet on offspring MASLD development and identifies mitochondrial dysfunction as a contributor to disease severity. In this setting, pharmacological compounds targeting mitochondrial dysfunction appear to have the greatest therapeutic potential.